A rare case report of dual mesiodens - Aditya Parampill; Reetika Rastogi; Rupinder Bhatia (Wolters Kluwer Medknow Publications, 2020)
Supernumerary teeth, a developmental anomaly when compared to the normal dentition, are characterized by the presence of an extra tooth or teeth. The most common supernumerary teeth are the mesiodens which is located in the middle region of the premaxilla, between the two central incisors. Its' prevalence differs between different racial groups, and in the population of India, it varies from 0.3% to 3.8%, with a ratio of 2: